“The impact of the South African national defence force armed forces week on local economies post Covid” - Kenny, Leon Rodney (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this applied research study was to assess the economic impact of the armed forces event on the Nelspruit local municipality. The rationale behind choosing this particular local municipality was based on the decision made by the Military Command Council (MCC) to designate Mpumalanga as the host province and Nelspruit as the host city. Regrettably, this occurrence took place during the initial phase of lockdown, known as level 1, and was integrated into the city's strategy for revitalizing the economy in the aftermath of the COVID- 19 pandemic. Despite being a military exercise, this event holds considerable significance as it exhibits the defining characteristics of hallmark events within its category. The research incorporated both secondary and primary data sources and a cost benefit analysis methodology was used. The results suggest that this particular event had a direct economic impact of R50 665 000 on the local economy, hence benefiting a multitude of businesses in the vicinity. Furthermore, the extended duration during which the troops of the South African National Defence Force (SANDF) were stationed in the host city created a favourable setting for the advancement of commercial activities. The study holds significance since it highlights the potential of the Department of Defence to contribute to socio-economic upliftment, as outlined in the Defence Act, Act 42 of 2002
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Armed forces event; Post covid; Local economies; Department of Defence; UCTD; SDG-8: Decent work and economic growth